2015
DOI: 10.7554/elife.06462
|View full text |Cite
|
Sign up to set email alerts
|

Kinetochore-independent chromosome segregation driven by lateral microtubule bundles

Abstract: During cell division, chromosomes attach to spindle microtubules at sites called kinetochores, and force generated at the kinetochore-microtubule interface is the main driver of chromosome movement. Surprisingly, kinetochores are not required for chromosome segregation on acentrosomal spindles in Caenorhabditis elegans oocytes, but the mechanism driving chromosomes apart in their absence is not understood. In this study, we show that lateral microtubule–chromosome associations established during prometaphase r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(158 citation statements)
references
References 48 publications
13
139
6
Order By: Relevance
“…We previously showed that chromosome segregation in the C. elegans oocyte is driven by an atypical kinetochore-independent mechanism . In this system, central spindle organization is essential for chromosome segregation (Muscat et al, 2015;McNally et al, 2016). In agreement, we show here that KLP-7 depletion leads to disorganized central spindles that correlate with impaired chromosome segregation.…”
Section: Klp-7 Is Globally Required For Normal Microtubule Dynamics Dsupporting
confidence: 73%
See 1 more Smart Citation
“…We previously showed that chromosome segregation in the C. elegans oocyte is driven by an atypical kinetochore-independent mechanism . In this system, central spindle organization is essential for chromosome segregation (Muscat et al, 2015;McNally et al, 2016). In agreement, we show here that KLP-7 depletion leads to disorganized central spindles that correlate with impaired chromosome segregation.…”
Section: Klp-7 Is Globally Required For Normal Microtubule Dynamics Dsupporting
confidence: 73%
“…The second important adaptation of the meiotic cell division process, as yet only observed in C. elegans oocytes, is kinetochore-independent chromosome segregation ). The precise mechanism of this atypical segregation is still unclear but involves microtubule-dependent forces exerted on chromosomes Muscat et al, 2015;McNally et al, 2016). The third specific adaptation of oocyte meiosis is polar body extrusion (PBE), which corresponds to an extremely asymmetric partitioning of the oocyte creating a tiny polar body with most of the cytoplasm maintained in the oocyte (Zhang et al, 2008;Dorn et al, 2010;Fabritius et al, 2011;Maddox et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work suggests that dynein on chromosomes may cause them to associate with microtubule minus ends (Muscat et al, 2015); another possibility, based on work in frog egg extracts (Yokoyama et al, 2014), is that MEL-28 itself links chromosomes to microtubules. More importantly, the mechanisms that elongate the spindle to separate homologous chromosomes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Although the outer kinetochore complex is required for proper chromosome alignment during early meiotic metaphase, even this complex disassembles before chromosomes separate during C. elegans meiosis. In this instance, lateral attachments to microtubule bundles along the sides of chromosomes and microtubule motor proteins may provide the major driving force [30, 31]. Intriguingly, neocentromeres formed on maize knob chromosomal elements during meiosis also do not require CenH3 for mediating attachments to the meiotic spindle [32].…”
Section: Loss Of An ‘Essential’ Chromatin Determinant Of Kinetochore mentioning
confidence: 99%